Infant-direct speech and mother-infant attention in depressed and nondepressed mothers - Santos, Ana Karina; dos Santos, Luiz Silva; Bussab, Vera Silvia Raad (Interação em Psicologia, 2020)
Postpartum depression (PPD) is associated with disturbances in many aspects of mother-infant interaction. We compared the content of the infant-directed speech (IDS), the expression of positive affection in the maternal voice and the attentional engagement in dyads of PPD and non-PPD mothers. Participants of this study were 80 mothers and their infants at 3-6 months. According to Edinburgh Postnatal Depression Scale (EPDS) 40 mothers were considered depressed. Mothers and their babies were videotaped during free play interactions. No significant differences were found among groups for the averages of all the categories. Two data sets representing optimal interactions styles were created based on the correlation coefficients. A linear regression analysis indicated that the mother`s years of education was a predictive factor for the occurrence of these interactive styles only for PPD mothers. PPD influenced mother-infant interaction when associated with maternal socio-demographic characteristics.